2017
DOI: 10.1016/j.celrep.2017.11.026
|View full text |Cite
|
Sign up to set email alerts
|

Co-chaperone BAG2 Determines the Pro-oncogenic Role of Cathepsin B in Triple-Negative Breast Cancer Cells

Abstract: Triple-negative breast cancer (TNBC) is considered incurable with currently available treatments, highlighting the need for therapeutic targets and predictive biomarkers. Here, we report a unique role for Bcl-2-associated athanogene 2 (BAG2), which is significantly overexpressed in TNBC, in regulating the dual functions of cathepsin B as either a pro- or anti-oncogenic enzyme. Silencing BAG2 suppresses tumorigenesis and lung metastasis and induces apoptosis by increasing the intracellular mature form of cathep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 36 publications
2
40
0
Order By: Relevance
“…It has been reported that BAG2 expression is increased in proteasome inhibitor-induced apoptosis [21]. Additionally, BAG2 plays a pro-oncogenic role in triple-negative breast cancer cells through its antiapoptotic activity [22]. In our study, LOXL1 stabilized BAG2 by blocking K186 ubiquitination, rendering glioma cells resistant to apoptosis in nonadherent conditions.…”
Section: Introductionsupporting
confidence: 50%
“…It has been reported that BAG2 expression is increased in proteasome inhibitor-induced apoptosis [21]. Additionally, BAG2 plays a pro-oncogenic role in triple-negative breast cancer cells through its antiapoptotic activity [22]. In our study, LOXL1 stabilized BAG2 by blocking K186 ubiquitination, rendering glioma cells resistant to apoptosis in nonadherent conditions.…”
Section: Introductionsupporting
confidence: 50%
“…2i ). These proteases, including MMP-3, MT1-MMP (MMP-14), cathepsin B and cathepsin D, have been reported to play important roles in cancer invasion, in vivo tumor growth and distant metastasis 39 41 .
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Shao et al (2018) showed that NEDD4 was needed for EGFR-dependent lung cancer cell migration and EGF-induced Cathepsin B secretion, as seen from a lack of Cathepsin B secretion in analysing a ligasedead mutant of NEDD4 and in NEDD4 knockdown experiments [148]. Finally, BAG2 was observed to process pro-Cathepsin B auto-activation and facilitated the secretion of pro-Cathepsin B to the cell surface, thereby increasing its metastatic potential in triple-negative breast cancer cells and thus linking BAG2 oncogenic signaling with Cathepsin B activation and tumor invasiveness [149].…”
Section: Signal Transduction Intermediates and Cathepsin Regulationmentioning
confidence: 90%